Religion And Religious Language A Religious Symbolism For Nonreligious Purposes - Aminullah Elhady (Pascasarjana IAIN Metro, 2018)
Religion is a very important thing in the people's lives. They need religion because of their weaknesses and limitations to face something outside themselves. Their limitations, especially in spiritual and metaphysical aspects, hence the people search for references which are considered hits, it is the religion. The spirit of religion in the collective life is to create the beneficiaries for the adherents. But, the religious symbolism is no less important than religion in life, so that religious symbols are greatly needed by the people. Moreover, religious symbolism is sometimes treated more than to the religion itself. Maybe public passion towards religious symbols more powerful than passion towards religion itself. Because it's not uncommon religious symbols are used for a variety of interests outside the religious interests, for example economic interests, political interests, and so on.